Implementasi Media Website Blogspot Dalam Pembelajaran PAI Siswa Kelas X Di SMK Nurul Iman Muntilan Tahun Ajaran 2024/2025 - Maulida Ulya; Priarni, Rina; Matori (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
This study aims to investigate how the Islamic Religious Education (PAI) class X students of the Computer and Network Engineering (TKJ) department at SMKinuruliimanimuntilanimagelangiforithei2024/2025 academic year are using the Blogspot website.As times change and information technology advances quickly, online or internet-based government media is emerging as one of the most effective ways to raise the standard of education.As a free blog platform, Blogspot is utilized to provide PAI materials in an interactive and engaging way.I In order to demonstrate the use of the Blogspot website media in PAIi learning, as well as its benefits and obstacles, this study combines a qualitative approach with a descriptive methodology.I The results demonstrate that the use of the Blogspot website as a learning tool in PAI can boost student engagement, give students flexible access to materials, and let teachers share learning resources in innovative ways.But there are problems. However,i challengesi suchi asi limitedi interneti accessi andi students'i technicali understandingi exist.i Thei implementationi ofi Blogspoti websitei mediai ini PAIi learningi fori classi Xi studentsi hasi ai positivei impacti buti requiresi supporti fromi variousi partiesi toi optimizei itsi utilizationi ini learning.Keywords:i Implementation; Blogspot; Educationi PAI.